Técnicas de reforzamiento de estructuras construidas de concreto que presentan deficiencias estructurales - Raigosa-Tuk, Eduardo (Instituto Tecnológico de Costa Rica, 2010)
The project named Reinforcement techniques of constructed concrete structures with structural deficiency has as a purpose to avoid unnecessary demolitions in concrete works that lack of design resistance or where the minimum steel was not placed, by the implementation of a complementary work. The compilation of the information was done by means of empirical experience in the reinforcement of works, data given by the professor guide, interviews to construction engineers, generating five application groups: foundations, columns, beams, slabs and walls. There are several limitations in this project and we can mention that the techniques can be applied to small and middle-sized works, one and maximum two height levels. The results show that works poorly constructed and a lack of information in most cases would be demolished but the techniques can be applied successfully to achieve the design standards or even exceed the capacity of each item. Thus the ultimate goal of the project is to propose tools to prevent the demolitions that have a negative impact on the cost of works, estimated time of delivery, generating environmental pollution from litter and debris, poor image of the professional or contractor.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2010.
Keywords: Producto; Concreto; Columna; Cimiento; Arquitectura